Thermal extraction of volatiles from the lunar regolith simulant NU-LHT-2M: Preparations for in-situ analyses on the Moon. (1st October 2019) - Reiss, P.; Grill, L.; Barber, S.J.
Abstract: The present work describes the end-to-end demonstration of enriching the lunar highland regolith simulant NU-LHT-2M with loosely adsorbed water, releasing this and other volatile compounds by thermal treatment in high vacuum, and identifying the released volatile species through mass spectrometry. This demonstration was performed to characterize how different sample conditions will affect the in-situ measurements performed by the ProSPA gas analysis instrument that is to operate near the lunar south pole on board the Russian Luna-27 lander. A laboratory breadboard was set up that allows testing of variable parameter combinations, such as different initial water contents, particle sizes, quantities, and bulk densities of the sample, as well as different heating rates. Three distinct temperature-dependent phases of outgassing were identified. Between −50 °C and 300 °C loosely adsorbed volatiles, mainly water in a mass fraction of around 0.1%–0.2%, were released from the samples. Above that the samples showed mineral decomposition which led to the release of trapped water, carbon dioxide, and hydrogen sulfide. It was shown that the gas pressure produced by outgassing of the volatile species in a continuously pumped system is noticeably higher if the sample is larger, contains smaller particles, or if a higher heating rate is applied. Highlights: NU-LHT-2M was hydrated with water in mass fractions around 0.1%. In a ProSPA-like laboratory breadboard the water was extracted by heating. NU-LHT-2M releases the added volatile water below a temperature of 300 °C. Different sample conditions develop different characteristic gas pressures. NU-LHT-2M releases trapped water, CO2, and H2 S from decomposition above 300 °C.